A retrospective review of paediatric cerebral venous sinus thrombosis in a South African tertiary hospital - Liebenberg, Hendrik Schalk (Stellenbosch : Stellenbosch University, 2016)
Thesis (MMed)--Stellenbosch University, 2016.